2007
DOI: 10.1007/s00414-007-0190-6
|View full text |Cite
|
Sign up to set email alerts
|

Single lymphocytes from two healthy individuals with mitochondrial point heteroplasmy are mainly homoplasmic

Abstract: The nature of mitochondrial DNA heteroplasmy is still unclear. It could either be caused by two mitochondrial DNA (mtDNA) haplotypes coexisting within a single cell or by an admixture of homoplasmic cells, each of which contains only one type of mtDNA molecule. To address this question, single lymphocytes were separated by flow cytometry assisted cell sorting and analyzed by cycle sequencing or minisequencing. To attain the required PCR sensitivity, the reactions were carried out on the surface of chemically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
1
11
0
1
Order By: Relevance
“…Amplification and subsequent sequencing of mtDNA were performed as described previously [28] but with primers L15908/H16432, L16268/H159, L16450/H429 and L314/H611 for PCR and sequencing [29]. Also, restriction fragment length analysis of nucleotide (nt) positions 303-310 was performed as described earlier [27].…”
Section: Samplesmentioning
confidence: 99%
“…Amplification and subsequent sequencing of mtDNA were performed as described previously [28] but with primers L15908/H16432, L16268/H159, L16450/H429 and L314/H611 for PCR and sequencing [29]. Also, restriction fragment length analysis of nucleotide (nt) positions 303-310 was performed as described earlier [27].…”
Section: Samplesmentioning
confidence: 99%
“…For example, Brandstätter and Parson demonstrated that the amplification strategy itself has a substantial impact on the appearance of heteroplasmy [26]. We also observed an interrelationship between the measured nucleotide ratios and the sequencing primers used [15], but other factors also have to be considered.…”
Section: Introductionmentioning
confidence: 68%
“…Moreover, low ratios of 1%, 2%, 3%, 4%, 7%, and 9% were created from 16093 C and 16093 T T lymphocytes to test the sensitivity of heteroplasmy detection. Instrument settings and the cell selection process were described previously [15], but selection of T lymphocytes was facilitated by fluorescent labeling. One row per plate was omitted to allow for positive and negative PCR and sequencing controls, respectively.…”
Section: Generation Of Artificial Heteroplasmy Using Cell Mixturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two types of heteroplasmy are recognized in mitochondrial genome: point and length heteroplasmy (Bendall and Sykes, 1995;Bendall et al, 1996). Point (sequence or site) heteroplasmy is defined by sequences presenting different bases at the same nucleotide position, which are usually observed in a sequence electropherogram as a superimposition of two different bases at this nucleotide position (Lutz-Bonengel et al, 2008). Length heteroplasmy is identified by repetitive tracts of consecutive cytosines, and has been found in four regions within the mtDNA control region (Bendall and Sykes, 1995;Lee HY et al, 2004;Forster et al, 2010).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%